Impacts of access to solar energy on rural households: An evaluation of a Netherlands supported programme in Burkina Faso - Gunther Bensch; Michael Grimm; Jörg Langbein; Jörg Peters (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
This impact report is part of an evaluation commissioned by the Policy and Operations Evaluation Department (IOB) of the Netherlands Ministry of Foreign Affairs. It belongs to a series of impact evaluations of renewable energy and development programmes supported by the Netherlands, with a focus on the medium and long term effects of these programmes on end-users or final beneficiaries. A characteristic of these studies is the use of quantitative research techniques, in combination with qualitative techniques, to get insight in the magnitude of effects. The purpose of the impact evaluations is to account for assistance provided and to draw lessons from the findings for improvement of policy and policy implementation. The results of these impact evaluations served as inputs to a policy evaluation of the "Promoting Renewable Energy Programme" (PREP) concluded in 2014.
Keywords: 330